2012
DOI: 10.4236/jep.2012.37067
|View full text |Cite
|
Sign up to set email alerts
|

A Situational Assessment of Socioeconomic Factors Affecting Solid Waste Generation and Composition in Freetown, Sierra Leone

Abstract: The generation of solid waste has become an increasing environmental and public health problem, especially in developing countries. These problems associated with the generation of solid waste are part of social changes where households play an important role. Invariably, these social changes influence the size, structure and characteristics of given households. This paper presents the findings of a study carried out in Freetown municipal area in Sierra Leone to assess socioeconomic factors affecting household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
4
20
1
1
Order By: Relevance
“…In this case, holding all other variables constant, a member increase in HH will increase the total HH waste generation by 0.12 kg/day, significant at 1%. Other studies have also found similar positive result (Afroz et al, 2011;Afroz, Masud, Akhtar, & Duasa, 2013;Gu et al, 2015;Khan et al, 2016;Maskey et al, 2016;Sankoh et al, 2012;Senzige et al, 2014;Sujauddin et al, 2008;Suthar & Singh, 2015;Trang et al, 2017). The more members in a HH, the more will be purchased and consumed that will ultimately result in higher waste generation.…”
Section: Waste Generationsupporting
confidence: 64%
See 4 more Smart Citations
“…In this case, holding all other variables constant, a member increase in HH will increase the total HH waste generation by 0.12 kg/day, significant at 1%. Other studies have also found similar positive result (Afroz et al, 2011;Afroz, Masud, Akhtar, & Duasa, 2013;Gu et al, 2015;Khan et al, 2016;Maskey et al, 2016;Sankoh et al, 2012;Senzige et al, 2014;Sujauddin et al, 2008;Suthar & Singh, 2015;Trang et al, 2017). The more members in a HH, the more will be purchased and consumed that will ultimately result in higher waste generation.…”
Section: Waste Generationsupporting
confidence: 64%
“…Studies by Maskey et al (2016) in the Philippines; Kayode and Omole (2011) in Nigeria and Sankoh et al (2012) in Sierra Leone showed employment status to have positive impact in generating more waste. Bandara, Hettiaratchi, Wirasinghe, and Pilapiiya (2007) in Sri Lanka revealed that number of employed people in HH contributed in increasing waste amount.…”
Section: Occupationmentioning
confidence: 99%
See 3 more Smart Citations